Design, in vitro release characterization and pharmacokinetics of novel controlled release pellets containing levodropropizine. (May 2014) - Cao, Qing-Ri; Piao, Yong-Nan; Choi, Jae-Seung; Liu, Yan; Yang, Mingshi; Cui, Jing-Hao
Abstract This study was performed to investigate the in vitro release characteristics of levodropropizine (LDP) from novel dual-coated sustained release (SR) pellets, and evaluate the pharmacokinetics of a novel controlled release (CR) preparation composed of the dual-coated SR pellets and immediate release (IR) LDP pellets. The dual-coated SR pellets composed of a drug-loaded nonpareil core, a sub-coating layer (HPMC 6cps) and an SR-coating layer (Aquacoat® ECD, Eudragit® RS 30D or Kollicoat® SR 30D) were prepared by a bottom-spray fluidized bed-coating method. The drug release from the dual-coated SR pellets coated with Aquacoat® ECD followed a zero-order profile in water, and the drug release was not affected by the coating level of the sub-coating layer and stable under the accelerated storage condition (40 °C, 75% RH) for 6 months. The CR preparation showed significantly decreased values of maximum drug concentration (Cmax) and elimination rate (K) than the reference product (LEVOTUS® SYR) but the similar bioavailability (F = 95.43%). The novel CR preparation presents promising delivery of LDP with an immediate and sustained release manner, with similar clinical effect as the commercial IR product.